História contemporânea do BNDES e o processo de internacionalização das empresas brasileiras - Pereira, Emelson Macedo Martins (2023)
The contemporary global economy is characterized by interconnected processes. There are several reasons for the internationalization of Brazilian companies, varying according to the moment, markets and entry modes. Broadly speaking, Brazilian internationalizations were tools to boost exports. Subsequently, this concept evolved and expanded its scope. Based on this, the present study aims to analyze the role of BNDES – National Bank for Economic and Social Development – in the recent process of the internationalization of Brazilian companies, specifically, investigating the case of multinationals, such as: JBS-Friboi, Gerdau, Vale and Marcopolo. To this end, a qualitative-quantitative approach will be used, employing the data collection method from the mentioned companies. The research results confirmed its hypotheses, demonstrated by the bank role in the internationalization business system, offering a solid platform for competitive instruments to reinforce the country's resilience and economic growth. It is noteworthy that even the most advanced companies in the internationalization process expressed the need for financial, operational, and technical support from BNDES. Furthermore, economic, commercial openness and the rise of foreign investment contributed to the modernization of Brazilian industry and the development of new capabilities. However, there are concerns over the national economy dependence and fluctuations vulnerability in the world economy